PERAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) SURABAYA DALAM MENINGKATKAN KESADARAN BENCANA MELALUI EDUKASI MITIGASI DI SEKOLAH DASAR - Regina Putri, Sonia; Muttaqin, Husnul (Universitas Islam Negeri Sunan Ampel, 2025)
Given its vulnerability to disasters, Indonesia necessitates an effective mitigation strategy to promote disaster mitigation awareness from an early age. This article analyzes the role of Surabaya Regional Disaster Management Agency (BPBD) in disaster mitigation education in elementary schools through qualitative approach with phenomenological method. Data were collected through in-depth interviews and observations in three elementary schools in Surabaya. The results of the study indicate that disaster education from an early age has been proven to shape responsive attitudes, reduce panic, and increase students' readiness in facing emergency situations. Effectiveness of this educational process can be seen from three main aspects: cognitive understanding improvement, attitude change, and practical skills of students in responding to disaster threats. However, challenges such as limited budget and human resources need to be overcome to expand the scope of the program. These findings prove that school-based education approach is effective in building sustainable disaster awareness.